Analisis Afiksasi dan Kesalahan Berbahasa Dalam Berita Daring Pos-Kupang:Kajian Morfologis - Elung, Maria Angelia; Pastika, I Wayan; Teguh, I Wayan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research is entitled "Analysis of Affixation in Pos-Kupang Online News". There are two problems analyzed in this research, namely the form and meaning of affixes contained in Pos-Kupang online news text and language errors contained in Pos-Kupang online news. The purpose of this research is to describe the form and meaning of affixes contained in Pos-Kupang online news and to find out the form of language errors contained in Pos-Kupang news text. The theory used in this research is morphology theory. Data collection in this study was conducted using the listening method and assisted by the free listening technique (SBLC) and continued with the note-taking technique. The data were analyzed using agih method and assisted by direct element division technique (BUL). The results of the analysis are presented with informal methods, followed by descriptive techniques and perspectives. Based on the analysis that has been done on Pos-Kupang online news, the following results are obtained (1) There are three affixes found in Pos-Kupang online news text, namely prefixes, suffixes, and confixes. (2) Several errors are found in Pos-Kupang's online news texts, first, spelling errors consisting of italicization, word writing errors, capitalization errors, and punctuation errors. Second, word choice errors in news writing. Third, sentence structure errors.)